2019
DOI: 10.1002/alr.22373
|View full text |Cite
|
Sign up to set email alerts
|

Hyams grading as a predictor of metastasis and overall survival in esthesioneuroblastoma: a meta‐analysis

Abstract: BackgroundEsthesioneuroblastoma (ENB), also known as olfactory neuroblastoma, represents up to 3% of all sinonasal neoplasms. Hyams histologic grading is a promising tool in predicting metastases and establishing prognoses for this complex tumor.MethodsA systematic literature search was performed in the PubMed, Ovid MEDLINE, and Cochrane databases. ENB patients with Hyams I‐II or III‐IV were categorized as low‐grade Hyams (LGH) or high‐grade Hyams (HGH), respectively. Binary and continuous random‐effects model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 52 publications
1
51
0
Order By: Relevance
“…These findings do not reflect what has been reported in larger series. Goshtasbi et al reported higher regional metastases rates in patients with high-grade tumors (18.2%) compared with those 28 Similarly, the authors reported lower 5-year overall survival rates in high-grade (54.2%) versus low-grade tumors (80.2%). Despite Hyams histopathologic grading system being shown to have prognostic significance in some studies, our study likely fails to demonstrate a difference in regional control.…”
Section: Discussionmentioning
confidence: 91%
“…These findings do not reflect what has been reported in larger series. Goshtasbi et al reported higher regional metastases rates in patients with high-grade tumors (18.2%) compared with those 28 Similarly, the authors reported lower 5-year overall survival rates in high-grade (54.2%) versus low-grade tumors (80.2%). Despite Hyams histopathologic grading system being shown to have prognostic significance in some studies, our study likely fails to demonstrate a difference in regional control.…”
Section: Discussionmentioning
confidence: 91%
“…The standard for pathological grading of ENB is the Hyams standard. At present, some studies have reported that pathological graded survival was significantly correlated and was an independent predictor of survival in patients with ENB [ 11 , 25 27 ]. For Chinese cohort, the tumor differentiation criterion based on the Hyams Grading System while the SEER cohort used the tumor differentiation grading scheme.…”
Section: Discussionmentioning
confidence: 99%
“…The standard for pathological grading of ENB is the Hyams standard. At present, some studies have reported that pathological graded survival was signi cantly correlated and was an independent predictor of survival in patients with ENB [19,[27][28][29]. For Chinese cohort, the tumor differentiation criterion based on the Hyams Grading System while the SEER cohort used the tumor differentiation grading scheme.…”
Section: Discussionmentioning
confidence: 99%